Unethical Marketing Practices and Emerging Consumerism in the Downstream Sector of the Nigerian Petroleum Industry (A Study of Bovas & Company Limited) (Journal of Management and Social Sciences, 2021)
The study focused on consumerism and unethical marketing practices of firms in the downstream sector of the Nigerian petroleum industry. It was inspired by the reported cases of unethical marketing practices and the emerging consumerism in the sector as observable in the consumers’ positive perception and patronage of Bovas & Company Limited’s Filling Stations, as against the dissonance expressed towards other Service Stations within its proximity. Survey research design was adopted and data was analysed through the use of correlation coefficient so as to ascertain the degree of relationship between the variables. The findings showed that unethical marketing practices has a positive effect on the emerging consumerism in the downstream sector of the petroleum industry in Nigeria. The study therefore recommended that relevant law enforcement agencies should improve on their monitoring and enforcement efforts geared towards checkmating unethical marketing practices of petroleum marketers in Nigeria, while petroleum marketers that indulge in unethical practices are advised to stop if their operations must remain sustainable.  Keywords    Consumerism, unethical marketing practices, petroleum industry